CD49f promotes proliferation of male dairy goat germline stem cells. (2nd February 2016) - Zheng, Liming; Zhu, Haijing; Mu, Hailong; Wu, Jiang; Song, Wencong; Zhai, Yuanxin; Peng, Sha; Li, Guangpeng; Hua, Jinlian
Abstract: Objectives: CD49f enhances multipotency and maintains stemness in embryonic stem cells (ESCs), however, whether it would be effective in mGSCs has remained unclear. Moreover, better standards for mGSC enrichment and purification are necessary. The present study was conducted to determine roles of CD49f in mGSC enrichment and regulation. Materials and methods: CD49f expression patterns were investigated in dairy goats. CD49f positive cells were purified and enriched using magnetic‐activated cell sorting (MACS), and characteristics of the cultured cells were assayed using alkaline phosphatase (AP) analysis, quantitative real‐time PCR (QRT‐PCR) and immunofluorescence analysis. Furthermore, the exogenous CD49f gene was transfected into mGSCs and its effects were analysed. Results: CD49f was found to be conserved in both mRNA and amino acid sequences and that it was an efficient marker for dairy goat mGSC identification, enrichment and purification. CD49f positive cells expressed higher levels of mGSC‐specific markers, and proliferated faster than CD49f negative cells. Overexpression CD49f promoted proliferation of dairy goat mGSCs, and Oct4 expression was upregulated; histone H3‐lysine 9 dimethylation (H3K9me2) was reduced. Conclusions: Taken together, our data suggest that CD49f plays novel and dynamic roles in regulating maintenance of pluripotency in mGSCs via Oct4 crosstalk and histone methylation dynamics, which may provide new solutions for mGSCs stability in vitro .